Studi Deskriptif Trend Tanaman Hias Kalangan Ibu-Ibu Di Kelurahan Sepe’e, Kecamatan Barru, Kabupaten Barru - Ruslan, Muh. Irbad; Nurlela, Mrs. (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2024)
This research aims to understand the increasing interest of the community, especially mothers towards ornamental plants in Sepe “e Village, Barru Regency. The research subjects are mothers who have a high interest in ornamental plants. Based on the results of the interview, the function of ornamental plants in mothers is to beautify the yard of the house to make it look beautiful and attractive when viewed besides that as an extension of their hobbies and love for plants which provide inner satisfaction for those who like to care for ornamental plants, in addition to beautifying the yard of ornamental plants can be sold for additional income to be useful. Another reason is because of the influence of family members who have hereditary cultivation of ornamental plants, the influence of the surrounding environment, the impetus of the hobby of caring for ornamental plants, the opportunity factor and the economic benefits of running a large ornamental plant business, and the prospect of an ornamental plant business that can run long not just seasonal. In addition to beautifying the environment, ornamental plants can also make the yard cool and beautiful and reduce air pollution, ornamental plants also have another function, namely opening up business opportunities for their owners.